Intelligence Stock Forecasting Using Neural Network - Pawar, Harish R; Gaikwad, Prasad G; Bombale, Umesh G; Jagtap, Dipak D; Durugkar, Santosh (International Journal of Computer Sciences and Engineering, 2014)
Future share market price prediction for any company mostly requires the help of AI and data mining techniques. The nature of any company almost depends upon fluctuation in share market. Some people think that buying or selling the stock of company is an act of gambling or any illegal activity but it is not the case instead it helps to us personally and for our countries growth also. However it is now possible to predict the future price by developing the effective pattern using neural network and data mining technique with the help of Back-propagation algorithm. By fetching historical data of any company from yahoo finance server and applying some data mining technique on it we are going to predict the future price.